Women, Minorities and Unions in the Public Sector - Leah, Ronnie (Labour / Le Travail, 1992)
The article reviews the book, "Women, Minorities and Unions in the Public Sector," by Norma M. Riccucci.
Keywords: BOOKS – Reviews; ETHNIC relations; Nonfiction; RICCUCCI; Norma M.; WOMEN; Minorities & Unions in the Public Sector (Book)